PENGARUH EKSPOR NON MIGAS DAN INVESTASI LANGSUNG NETTO TERHADAP PDB NON MIGAS - Fahrul Riza (Journal of Business & Applied Management, 2015)
This paper measured the effect of export value from agricultural, mining, manufacturing and direct investment through the value of Indonesia’s non oil and gas Gross Domestic Product (GDP) from 2005 to 2013. By using ordinary least squre method, it showed that export from agricultural and minimg sector have significat effect to the value of non oil and gas Indonesia’s GDP. However export form manufacturing and direct investment didn’t show any significant effectKeywords :Non Oil and Gas Export, Investment Netto, Produk Domestik Bruto (PDB), Ordinary Least Square